Studies of biofilms and phenotypic characteristics of Candida fungi - E. M. Lenchenko; N. P. Sachivkina (Ветеринария сегодня)
Yeast-like fungi of the genus Candida are causative agents of the infectious pathology of the mucous membrane of the gastrointestinal, respiratory, urogenital tracts and skin of mammals, sepsis, and disseminated infection in birds. The search and testing of multilevel algorithms for biofilm identification when exposed to chemotherapeutic and disinfectant drugs for blocking the synthesis or destruction of the intercellular matrix in the development of superficial, deep and systemic candidiasis of animals are relevant for developing and improving diagnostic and antiepidemic measures. It was established that the formation of biofilm heterogeneous structure comprises multiple stages implementing the processes of intercellular communication due to the synthesis of a polymer matrix composites. Optical microscopy revealed a three-dimensional structure of biofilms in the form of a dense network consisting of yeast cells, hyphal and pseudohyphalic forms surrounded by an intercellular polymer matrix. Candida spp. pathogenicity factors contribute to infection of susceptible species due to adhesion, invasion, secretion of hydrolases, dimorphism. Formation of mono-species or poly-species biofilms of microorganisms, including Candida spp., causes the development of superficial, deep and systemic candidiasis. Detection of a large amount of yeast and micellar phases in C. albicans and C. africana isolates was a differential sign of a significant degree of colonization of the mucous membranes of the larynx, pharynx, and tonsils in case of local and systemic pathologies in pigs. The results of studies of the biofilm heterogeneous structure and phenotypic signs of yeast-like fungi can be used in a comparative study of biological characteristics and the identification of common patterns and differential signs of microorganisms, optimization of mycological diagnostics, and also in the development of antimycotic drugs.